Gestión administrativa y su influencia en el rol de las secretarias del departamento de Talento Humano del GAD Municipal de Puebloviejo - Pozo Chavez, Tania Lisbeth (2022)
This study aims to determine the Administrative Management and its influence on the role of the secretaries of the human talent department of the Municipal Government of Puebloviejo, knowing that the role of the secretaries is crucial in the institution as they are responsible for drafting, files and other daily activities entrusted to them. For a correct functioning and agility of all the processes there must be an efficient administrative management that plans, directs, controls the flow and veracity of the detailed information, thus providing an optimal work environment where each one of them has defined responsibilities and detect in time any anomaly that may arise in the flow of information at the time of executing the tasks entrusted to them. In the theoretical context, relevant topics were addressed with bibliographic-documentary support that affirm the importance of administrative management, as well as the important role played by secretaries today, since they contribute with efficiency, performance and productivity in general, optimizing time and resources in their functions. For the development of this research, the methods used were inductive, which provided the solution to the development of the problems encountered, and deductive because it determined the general basic concepts used through previous research already carried out, to establish relevant conclusions based on the information obtained. It will also support the content of a questionnaire of eight questions asked to the secretaries in the research process carried out in the GAD.